A new health-related quality of life instrument for leukemia: will it be widely adopted soon? - Junhua Yu; Joanna Cheung (BioExcel Publishing Ltd, 2013)
Background: The rapid escalation in the treatment costs of cancer, as well as modest survival gains of the treatment, drive an emerging need to determine the value of cancer therapy from the perspectives of stakeholders such as patients, payers, There is an increasing role for health-related quality of life (HRQoL) evidence in guiding a clinician's treatment decision and influencing a payer's coverage decision. However, in the field of leukemia research, there has been a paucity of validated leukemia-specific measurement tools to assess HRQoL which has recently been filled by FACT-Leu questionnaire. This instrument is a new pharmacoeconomics tool that will help address part of the question of the value of leukemia therapy. Strengths and weaknesses: The developers of FACT-Leu set out to create a culturally relevant HRQoL tool for acute and chronic leukemia. Item generation included inputs from participants from South America, Europe, and North America, but demographic data were not available. Hoping to answer the need for leukemia-specific HRQoL measurements tools, the authors supplemented the widely used 27-item FACT-G with a 17-item leukemia sub-scale to createFACT-Leu. The study lacks sound data to support convergent validity. In HRQoL research, convergent validity generally refers to whether the HRQoL scale relates (converges) to other measures of related constructs, which are typically quantitatively assessed using Spearman and Pearson correlations. Conclusions: FACT-Leu is a relatively new HRQoL measurement tool that attempts to fill the gap for leukemia-specific HRQoL measurement tools. The scale has already been implemented in an American-based clinical trial assessing the use of a tyrosine kinase inhibitor and HRQoL in chronic myeloid patients. Although this tool fills a void for an HRQoL instrument for leukemia, its future value in informing clinical decision-making will be limited unless it can help clinicians and patients to easily interpret HRQoL outcomes and distinguish implications of different numerical scales.